Problem psychomanipulacji religijnej w kontekście globalnej pentekostalizacji chrześcijaństwa - Kobyliński, Andrzej (Człowiek i Społeczeństwo, 2022)
This article focuses primarily on a synthetic presentation of the global process of pentecostalization as well as the analysis of the selected religious abuses that occur in Christian communities on the grounds of emotional and syncretic Pentecostal religiosity. Over the last two decades, the interest in the problem of psychomanipulation and religious abuses has grown significantly in the Catholic Church and in other Christian denominations. This phenomenon is subject to in-depth philosophical, psychological, sociological, theological and cultural analyses, particularly in countries such as the United States, France or Great Britain. Religious abuse, also known as spiritual abuse or spiritual violence, refers to various forms of psychomanipulation, power, and control over people through religion, faith, or beliefs. The risk of abuse is especially high in the context of contemporary syncretic Neo-Pentecostal religiosity which is characterized by the so-called praying in tongues, miracles, emphasizing the presence of the devil in the world, exorcisms, prayers of deliverance, healings, introducing participants of prayer meetings into altered states of consciousness, etc. In the application of such methods, the principle of informed consent, which in medical practice applies to the relationship between doctors and patients, should be one of the basic ethical norms implemented with the aim of protecting against religious abuse and regulating the relationship of leaders to members of their communities.